Production Practices and Marketing Strategies of Ginger (Zingiber officinale L.) in Southern Philippines - Morados, Alexander N. (Future Science / FSH-PH Publications, 2024)
Ginger (Zingiber officinale L.) is one of the priority vegetables and most processed functional food in many parts of the the Philippines. This study assessed the production practices and marketing strategies of ginger in Northern Mindanao from October 2022 to October 2023. It utilized a validated survey questionnaire administered to 160 registered farmers in the provinces of Bukidnon, Camiguin, Lanao del Norte, Misamis Occidental and Misamis Occidental supplemented with key informant interviews, focus group discussion and secondary data. Findings showed that majority of the respondents belong to age bracket 50-59 years old, earn a monthly family income range of PhP 9,520.00 to PhP 19,040.00 and obtain basic education diploma. The respondents “Always Practiced” the recommended production practices and “Moderately Practiced” the suggested marketing strategies for the commodity by the Department of Agriculture. There is a significant relationship between production practices and marketing strategies. There is a significant differnce on the extent of marketing strategies when grouped according to age and monthly and highest educational attainment. Challenges include low market price and high cost of farm inputs which are threats productivity and profitability of the ginger industry.